Proposição de um framework conceitual baseado na dimensão tecnológica para cidades inteligentes - Silva, Rafaela Macedo (2018)
Considering the urban population growth and the scarcity of resources, municipalities faces challenges to provide basic services to the population. In this scenario the Smart City concept has become popular, since while the urban concentration raises problems such as congestions, pollution, social inequalities and limited access to public services, it also allows the massive interconnection of people using the data communication network. This interconnection is characterized by the intensive use of the information and communication technologies (ICT), which associated with the internet of things (IOT) sensors, software intelligence, human capital and other factors, helps the decision making, contributing for the resource efficiency. From this context, the study aims to answer the question: “Which elements should be considered in order to structure a smart city from the technological dimension?”. Accordingly, based on the technological dimension, it aimed to present a Framework with the structuring elements of an intelligent city. Therefore, three interconnected and sequential studies were performed. The first one consisted of a bibliometric study that brings a systematic view of the historical knowledge presenting eight (8) groups of study. The second one complemented the theoretical knowledge by including recent and high impact articles, which ones were grouped in seven (7) clusters, and then analyzed using systematic review techniques, as the result it was presented topics for future researches. The third one was based on the previous studies to formulate questions that was applied to experts in the area of Smart Cities. The interviews content was analyzed and crossed with the theory and as a dissertation contribution it was presented a conceptual Framework with the synthesis of the elements that should be considered for the structuring of a Smart City from the technological dimension. The results shown in this dissertation can be considered as a guidance for the public managers, researches and other stakeholders.